Evaluación de herbicidas en hortalizas: zanahoria, coliflor y remolacha (II sem 89 a I sem 90). - Monroy González, R.A.; Ardila Romero, G.; Fuentes Delgado, C.L. (Instituto Colombiano Agropecuario - ICA, 2018)
Coliflor-Brassica oleracea